Prozeus enterprise: One stop centre wireless portable charger / Nurul Usni Iman Abd Jamlus [et al.] - Abd Jamlus, Nurul Usni Iman; Ahmad Rosli, Nurin Amani; Abdul Ghani, Nurul Alia Najihah; Ahmad, Nur Natasya Adlina; Mohamad Nizam, Nur Syafira (2017)
In the 21st century today many engineer has constructed and incredible creations of electrical gadget in various forms and material. To compete with that, we have developed an idea that could be beneficial to people by selling a product called wireless portable charger, as we know that portable chargers are commonly used these days and it will be advance to be wireless.